Behavior of the ε-Ga2O3:Sn Evaporation During Laser-Assisted Atom Probe Tomography. (August 2021) - Chabanais, Florian; Di Russo, Enrico; Karg, Alexander; Eickhoff, Martin; Lefebvre, Williams; Rigutti, Lorenzo
Abstract: Abstract : The measurement of the composition of ε-Ga2 O3 and the quantification of Sn doping in ε-Ga2 O3 :Sn by laser-assisted atom probe tomography (APT) may be inaccurate depending on the experimental conditions. Both the role of the laser energy and surface electric field were investigated, and the results clearly indicate that deviations from stoichiometry are observed changing the electric field conditions during APT. The measured atomic fraction of Ga can change from 0.45 at low field to 0.38 at high field, to be compared with the expected 0.4. This was interpreted in terms of preferential evaporation of Ga at high field and deficit of O at low field, which was caused by the formation of neutrals. The quantification of Sn-doping is accurate at low-field conditions, with an overestimation of the detected Sn-metallic fraction at high field. This suggests that Sn has a higher evaporation field compared to Ga. Finally, multiple detection events were in-depth studied, revealing that three dissociation reactions occur during APT: GaO 2+ → Ga + + O + ; Ga2 O2 2+ → Ga + + GaO2 + ; Ga3 O2 2+ → Ga + + Ga2 O2 + . Nevertheless, only 2% of the detected events are related to such dissociation reactions, too small a fraction to fully explain the observed deviation from the stoichiometric composition in ε-Ga2 O3 .